Optimization and validation of an existing, surgical and robust dry eye rat model for the evaluation of therapeutic compounds. (May 2016) - Joossen, Cedric; Lanckacker, Ellen; Zakaria, Nadia; Koppen, Carina; Joossens, Jurgen; Cools, Nathalie; De Meester, Ingrid; Lambeir, Anne-Marie; Delputte, Peter; Maes, Louis; Cos, Paul
Abstract: The aim of this research was to optimize and validate an animal model for dry eye, adopting clinically relevant evaluation parameters. Dry eye was induced in female Wistar rats by surgical removal of the exorbital lacrimal gland. The clinical manifestations of dry eye were evaluated by tear volume measurements, corneal fluorescein staining, cytokine measurements in tear fluid, MMP-9 mRNA expression and CD3 + cell infiltration in the conjunctiva. The animal model was validated by treatment with Restasis® (4 weeks) and commercial dexamethasone eye drops (2 weeks). Removal of the exorbital lacrimal gland resulted in 50% decrease in tear volume and a gradual increase in corneal fluorescein staining. Elevated levels of TNF-α and IL-1α have been registered in tear fluid together with an increase in CD3 + cells in the palpebral conjunctiva when compared to control animals. Additionally, an increase in MMP-9 mRNA expression was recorded in conjunctival tissue. Reference treatment with Restasis® and dexamethasone eye drops had a positive effect on all evaluation parameters, except on tear volume. This rat dry eye model was validated extensively and judged appropriate for the evaluation of novel compounds and therapeutic preparations for dry eye disease. Highlights: Optimization of a robust, low maintenance dry eye animal model. Implementation of clinically relevant evaluation parameters. Validation with cyclosporine A and dexamethasone. Model suitable for evaluation of novel compounds.